Regulation of the microbiota in the gut of Drosophila melanogaster - Matos, Gonçalo Santos (2021)
"Animals harbour complex bacterial communities in their gut, termed “gut microbiota”, which have a great impact on their biology. This includes modulating traits such as development, immunity, metabolism or behaviour. The species composition and frequency of gut bacteria differ from those of the environment of the animal suggesting that gut bacteria have evolved specific mechanisms to live in this niche. Understanding the mechanisms that regulate the gut microbiota has been an important question in the field of symbiosis."